Lamotrigine Induced Drug Reaction with Eosinophilia and Systemic Symptoms (Dress) Syndrome, Dysphagia and Steroid Pulse Therapy. A Case Report - Shahida Naz; Raza Ullah; Haleema (Gandhara University, 2023)
OBJECTIVES Adverse drug reactions are common, and dermatological manifestation is a common indicator. The potentially lethal "Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) syndrome" is one example of severe drug reactions manifesting within weeks after drug intake. It is characterized by "fever, skin rash, lymphadenopathy, eosinophilia and systemic symptoms". We present a case of DRESS syndrome secondary to anticonvulsants lamotrigine associated with dysphagia and responding to steroid pulse therapy.